The farmer's fruit-garden - Sanford, Lawrence V. (My University, 1904)
Introduction: In this age when there is so much scientific as well as practical knowledge available in regard to the culture of small fruits, there are few excuses which the farmer of today may offer for not having a fruit-garden upon his farm that will furnish sufficient small fruits for his table. In the earlier days it was supposed to be too much work and bother for the farmer to raise small fruits, but that day is, we are glad to say, passing away although there are some who still cling to the old ideas. It is the aim of this paper to farther dispel the doubts remaining in the mind of the farmers as to their ability to raise small fruits, by presenting some facts in regard to the cultivation and care of small fruits.
Citation: Sanford, Lawrence V. The farmer's fruit-garden. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Gardening; Fruits; Agricultural Techniques; Theses; Manuscripts (documents)